Mechanochemically synthesized Fe2B nanoparticles embedded in SiO2 nanospheres - Mertdinç, Sıddıka; Ağaoğulları, Duygu; Öveçoğlu, M. Lütfi (Elsevier BV, 2018)
Abstract This study reports on the preparation of diiron boride (Fe 2 B) powders via mechanochemical synthesis (MCS) followed by a purification step and on the embedment of pure Fe 2 B nanoparticles into silica (SiO 2 ) nanospheres. Fe 2 O 3 , B 2 O 3 and Mg powders used as starting materials were blended in stoichiometric amounts and mechanochemically synthesized up to 7 h in a high-energy ball mill. As-synthesized powders were purified from the undesired Mg-based by-products by HCl leaching. After that, pure Fe 2 B nanoparticles with sizes of smaller than 40 nm were embedded in SiO 2 nanospheres using a tetraethyl orthosilicate (TEOS) and ammonia (NH 3 ) containing solution. Characterization investigations of the as-synthesized, leached and SiO 2 -embedded powders were carried out using X-ray diffractometer (XRD), scanning electron microscope/energy dispersive spectrometer (SEM/EDS), particle size analyzer (PSA), transmission electron microscope (TEM), Fourier transform infrared spectrometer (FTIR) and vibrating sample magnetometer (VSM). The average particle size of the Fe 2 B incorporated SiO 2 nanospheres was measured as about 330 nm. Magnetic measurements revealed that pure Fe 2 B powders and their SiO 2 -embedded samples had soft ferromagnetic behaviour with coercivity of 125 and 168 Oe, respectively.